2013
DOI: 10.1371/journal.pone.0056139
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF MS Distinctly Differentiates Nontypable Haemophilus influenzae from Haemophilus haemolyticus

Abstract: Nontypable Haemophilus influenzae (NTHi) and Haemophilus haemolyticus exhibit different pathogenicities, but to date, there remains no definitive and reliable strategy for differentiating these strains. In this study, we evaluated matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) as a potential method for differentiating NTHi and H. haemolyticus. The phylogenetic analysis of concatenated 16S rRNA and recombinase A (recA) gene sequences, outer membrane protein P6 gene s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…However, it may not be able to provide sufficient resolution for subtyping of bacterial pathogens, which is often performed in public health microbiology laboratories for disease surveillance and other large epidemiological surveys. The power of MALDI-TOF for identification of H. haemolyticus and H. influenzae is highly dependent on a well-defined reference spectrum for H. haemolyticus in species databases, which varies between laboratories (35,36). Its utility in discriminating between H. haemolyticus and H. influenzae remains to be further validated.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may not be able to provide sufficient resolution for subtyping of bacterial pathogens, which is often performed in public health microbiology laboratories for disease surveillance and other large epidemiological surveys. The power of MALDI-TOF for identification of H. haemolyticus and H. influenzae is highly dependent on a well-defined reference spectrum for H. haemolyticus in species databases, which varies between laboratories (35,36). Its utility in discriminating between H. haemolyticus and H. influenzae remains to be further validated.…”
Section: Discussionmentioning
confidence: 99%
“…This is rather different from the observation of Sethi et al 1 , who reported 145 cases of new H. influenzae acquisition versus 1503 cases of no new strain acquisition (8.7%). Incorrect identification of H. haemolyticus as H. influenzae cannot be the cause of this difference, because we used the advanced version of database for MALDI-TOF MS identification 10 . However, in the study of Sethi et al 1 , COPD patients were requested to come for screening for bacterial presence in sputum at regular monthly intervals regardless of their health status, unlike in our study, where sputum was sampled from patients who sought medical care or were treated during hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…If this technology is available and suitable reference spectra are included in the database, MALDI-TOF-MS has the potential to provide diagnostic results with sufficient reliability for the diagnostic routine situation [40][41][42]. For less well-equipped laboratories, FISH might be a cost-effi cient and easy-to-perform alternative but will not provide conclusive results in all instances [40].…”
Section: Discussionmentioning
confidence: 99%
“…Suitability of MALDI-TOF-MS for the discrimination of H. infl uenzae from H. haemolyticus has been described in 2013 [40,41] and confi rmed in 2014 [42]. Nevertheless, the availability of a well-defi ned reference spectrum for H. haemolyticus in the applied database is an important prerequisite for this.…”
Section: Matrix-assisted Laser-desorption-ionization Time-of-flight Mmentioning
confidence: 99%